Hotel Mumbai [videorecording (DVD)] - Maras, Anthony; Maras, Anthony; Patel, Dev, 1990-; Hammer, Armie, 1986-; Boniadi, Nazanin, 1980- (Universal Pictures Home Entertainment, 2019)
Dramatized portrayal of the 2008 terrorist attacks at the Taj Mahal Palace Hotel in Mumbia, India.